Peningkatan Pemahaman Konsep Siswa Kelas V dengan Pemanfaatan Media Pembelajaran Geogebra - Luqmanul Hakim; Markhamah Markhamah; Sutama Sutama (AS-SABIQUN, 2022)
The purpose of this research is to create a learning media for the concept of geogebra to improve students' mathematical understanding of the material of spatial structure. The things tested in this study were validity, practicality, and effectiveness. This research method is R&D with a 4-D model, namely defining, designing, developing and distributing. However, in this study only up to the development stage. Based on the research that has been done, the result is that the average score of media experts is 3.6, material experts are 3.6, which means the results are very good. Furthermore, the practicality score obtained from the teacher's response questionnaire is 89,93% and the student's is 78,67%. Furthermore, the results of the effectiveness of learning media get 90% of students who get complete learning using geogebra learning media.